2016
DOI: 10.1007/s00401-016-1630-5
|View full text |Cite
|
Sign up to set email alerts
|

Soluble phospho-tau from Alzheimer’s disease hippocampus drives microglial degeneration

Abstract: The role of microglial cells in the development and progression of Alzheimer’s disease (AD) has not been elucidated. Here, we demonstrated the existence of a weak microglial response in human AD hippocampus which is in contrast to the massive microglial activation observed in APP-based models. Most importantly, microglial cells displayed a prominent degenerative profile (dentate gyrus > CA3 > CA1 > parahippocampal gyrus), including fragmented and dystrophic processes with spheroids, a reduced numerical density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
149
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(172 citation statements)
references
References 66 publications
(115 reference statements)
17
149
0
Order By: Relevance
“…The utilization of post mortem human samples was approved by the corresponding biobank ethics committees and the “Comite de Etica de la Investigacion (CEI), Hospital Virgen del Rocio”, Seville, Spain. All the subjects (Braak 0, II, III–IV and V–VI) in this study are identical to those reported by us previously (Sanchez‐Mejias et al, 2016). All cases were scored for Braak tau pathology.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…The utilization of post mortem human samples was approved by the corresponding biobank ethics committees and the “Comite de Etica de la Investigacion (CEI), Hospital Virgen del Rocio”, Seville, Spain. All the subjects (Braak 0, II, III–IV and V–VI) in this study are identical to those reported by us previously (Sanchez‐Mejias et al, 2016). All cases were scored for Braak tau pathology.…”
Section: Methodssupporting
confidence: 88%
“…Therefore, altogether our data support the idea of dysfunctional astroglial cells in the context of AD. In this sense, we have recently reported that microglial cells in the hippocampus of AD brains display a degenerative phenotype (Sanchez‐Mejias et al, 2016). Therefore, the functional impairment of glial cells in AD as a potential driver of disease progression deserves particular consideration.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instances, a recent study reported that microglial cells in the hippocampi of severely affected Braak stage V-VI samples were no longer even associated with neuritic plaques or with the vascular amyloid, highlighting the range of microglial alterations [40]. …”
Section: Discussionmentioning
confidence: 99%